COVID-19 :Correlation Between CRP and LDH to Disease Severity and Mortality In Hospitalized COVID-19 Patients - Tjahyadi, Rizal Muldani; Astuti, Triwahju; Listyoko, Aditya Sri (RSUP Dr. Kariadi, 2020)
Background and Objective:COVID–19 is a newly emerging disease and considered an emergency health problem, worldwide.It has a wide range of clinical features, from mild fever to severe respiratory failure that leads to a higher mortality rate. Previous studies state that CRPhas a very strong positive correlation with the diameter of the lung lesion, and in intensive care patients had a higher level of LDH. This study aims to determine the correlation between CRP, LDH and disease severity and mortality in hospitalized COVID-19 patients. Methods: We conducted a retrospective cohort, a single-center study including 69 laboratory-confirmed patients in our hospital in Malang City, Indonesia from April - June 2020. Result: Subjects consisted of 26 patients (37.7%) in the mild-moderate group and 43 patients in severe group (62.3%).Statistical analysis showed CRP and LDH associated with disease severity (p=0.011 and p<0.001). Analysis of CRPand LDH in survivor and non-survivior group showed that CRP and LDH also asscociated with mortality in hospitalized COVID-19 patients (p=0.034 and 0.002). We also evaluate CRP and LDH with degrees of hypoxemia by assessed P/F ratio. Statistical analysis showed that CRP did not correlate with degrees of hypoxemia (p=0.079) but LDH inverse correlate with degrees of hypoxemia (p<0.001, pearson correlation = -0,489) Conclusion: In our retrospective cohort study demonstrated LDH and CRP can be a crucial indicator to predict severity and mortality for hospitalized COVID-19 patients and LDH may usefull test for predict early identification of patients who become respiratory failure or ARDS. Keywords: COVID-19, LDH, CRP, P/F Ratio